Nomadic Norwegian Architecture: An Historical and Contemporary Study of Prefabricated Norwegian Whaling Settlements in the Southern Hemisphere - France, Hannah (11676211) (2010)
The early 1900’s saw a Norwegian Whaler’s base formed on Stewart Island where they shipped prefabricated buildings from Norway to create a settlement. The majority of these kitset buildings are still standing and apparently have had little modification from their original form. These buildings have no documentation of their materials, suitability of site or analysis of their current condition in this foreign environment. Initial research found one book by J.P.C Watt from the 1980’s which researches the Ross Sea whalers with little focus on the architecture or design. The book documents the movements of the buildings from their original service as a whaling station in the early 1900’s. This is an interesting ensemble of nomadic buildings, foreign to New Zealand, being moved around consistently and yet still remaining in the country today. Through the investigation of materiality, tectonics and individual building elements the research demonstrates how the buildings reacted to their nomadic inhabitants and also how the materials allowed for a sense of personal belonging to occur. This research aims to explore the materiality of Norwegian portable architecture and the material’s present conditions. It establishes that the nomadic/temporal nature of the Norwegian kitset buildings were not adapted to fit the New Zealand context and documents these buildings for future reference. The first step is literature research and design exploration of Norwegian kitset materials, tectonics and components. In the second step, analysis of case studies is conducted. Findings have been judged upon functionality, and therefore the design is a result of the site context and research.